2007
DOI: 10.1016/j.otohns.2007.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Kimura Disease: Diagnosis and Prognostic Factors

Abstract: A preoperative decision based on our diagnostic criteria and prognostic factors should lead to better therapeutic outcomes for Kimura disease, for which a definitive treatment policy has never been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 13 publications
1
41
3
1
Order By: Relevance
“…A previous report had shown that a high PB eosinophil count can be used as a risk factor for recurrence in KD [23]. In our study, the PB eosinophil count at diagnosis was higher in patients with recurrence than in patients without recurrence, but the difference did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 86%
“…A previous report had shown that a high PB eosinophil count can be used as a risk factor for recurrence in KD [23]. In our study, the PB eosinophil count at diagnosis was higher in patients with recurrence than in patients without recurrence, but the difference did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 86%
“…Other sites such as the oral cavity, axilla, groin, limbs, and trunk have also been described, but the involvement of the respiratory tract is rare. To our knowledge, 10 cases of KD centered around the epiglottis have appeared in the English and Japanese literature [7][8][9][10][11][12][13][14][15][16]. Our case provides an additional example (Table 1).…”
Section: Discussionmentioning
confidence: 85%
“…Iwai et al had described blood eosinophilia at mean count of 35.2% with elevated IgE in all Kimura's cases. 5 The patient reported here also has eosinophilia and elevated serum IgE levels. Kimura's disease can be mistaken easily for a malignant tumor like acute lymphocytic leukemia, T-cell lymphoma, Hodgkin's etc., among others.…”
Section: Discussionmentioning
confidence: 61%